EZHCheckup / Noreha Che Sidik ... [et al.] - Che Sidik, Noreha; Elias, Shamsul Jamel; Jaafar, Nurul Atikah; Haliza, Hafiqa Eliya (Universiti Teknologi MARA, Kedah, 2019)
EZHCheckup is an online student health medical checkup system to provide an easy platform for the registered students to send their completed medical checkup document online to Unit Kesihatan. The medical checkup can be done at any government or private clinics or hospitals by using the form provided in the application letter. This system provides mobility features for the students to access the system anywhere, anytime without manually sending them to Unit Kesihatan. The system allow the staffs to analyze the compilation of student medical forms easily and eventually can generate the report about the student’s health information such as anthropometric data, classification of diseases (ICD 10) based on their gender and courses. These information provide us to plan proactive healthy life style programs accordingly to give proactive solutions to students so they can manage their healthcare proficiently. This system is cost effective in terms of time, manpower and material usage as it was operated online. Moreover, it has the ability to trace the completeness submission of medical checkup for each registered students. It is a user friendly and efficient system compared to previous time-consuming manual system and can be commercialized to other agencies such as IPTA/IPTS, and any organizations or companies whom dealing with medical checkup for their employees.